Implementing A Community-Based Youth Digital Literacy Training Program For Community Empowerment In Pakistan - Ayesha Noor; Ahmed Raza Khan (Yayasan Cendekiawan Digital Indonesia, 2026)
The lack of structured digital literacy mentoring remains a challenge for youth communities in semi-urban Pakistan, despite increasing access to mobile devices. This situation has implications for low levels of targeted digital communication skills, critical information evaluation, and responsible online interaction practices. A community-based training program was conducted at a youth center in Lahore with 28 participants aged 16–22 years to strengthen practical digital competencies while encouraging social participation. The program was implemented through a participatory approach that included initial needs discussions, guided practice workshops, and collaborative reflection sessions focused on digital communication, media ethics, and simple content production for community activities. Data were collected through observation notes, reflective feedback, and pre- and post-program questionnaires, and then analyzed using descriptive comparisons enriched with thematic interpretation. During the program, participants demonstrated increased confidence in using online collaborative tools and a tendency toward more structured communication. These changes were accompanied by a stronger awareness of digital responsibility in social interactions. Although conducted on a limited scale, this experience provides an overview of contextual digital literacy training practices and has the potential to serve as a reference for developing technology-based youth empowerment models across various global communities.